The girl who drank the moon - Barnhill, Kelly Regan (Chapel Hill, North Carolina : Algonquin Young Readers, 2016)
Every year, the people of the Protectorate leave a baby as an offering to the witch who lives in the forest. They hope this sacrifice will keep her from terrorizing their town. But the witch in the forest, Xan, is kind and gentle. She shares her home with a wise Swamp Monster named Glerk and a Perfectly Tiny Dragon, Fyrian. Xan rescues the abandoned children and delivers them to welcoming families on the other side of the forest, nourishing the babies with starlight on the journey. One year, Xan accidentally feeds a baby moonlight instead of starlight, filling the ordinary child with extraordinary magic. Xan decides she must raise this enmagicked girl, whom she calls Luna, as her own. To keep young Luna safe from her own unwieldy power, Xan locks her magic deep inside her. When Luna approaches her thirteenth birthday, her magic begins to emerge on schedule -- but Xan is far away. Meanwhile, a young man from the Protectorate is determined to free his people by killing the witch. Soon, it is up to Luna to protect those who have protected her -- even if it means the end of the loving, safe world she's always known
"Published simultaneously in Canada by Thomas Allen & Son Limited"--Title page verso
Middle School
640
Ages 10-14
4 to 6
Accelerated Reader
Keywords: Witches -- Juvenile fiction; Child sacrifice -- Juvenile fiction; Abandoned children -- Juvenile fiction; Magic -- Juvenile fiction; Friendship in children -- Juvenile fiction; Abandoned children; Child sacrifice; Friendship in children; Magic; Witches; Fantasy fiction; Fantasy fiction; Fantasy fiction; Fiction; Juvenile works